Pomegranate juice fermented by tannin acyl hydrolase and Lactobacillus vespulae DCY75 enhance estrogen receptor expression and anti-inflammatory effect - Akter, Reshmi; Chan Ahn, Jong; Nahar, Jinnatun; Awais, Muhammad; Ramadhania, Zelika Mega; Oh, Se-Woung; Oh, Ji-Hyung; Kong, Byoung Man; Rupa, Esrat Jahan; Lee, Dong Wong; Yang, Deok Chun; Chan kang, Se (Frontiers in Pharmacology, 2022)
Phenolics are phytochemicals in plants, fruits, and vegetables have potential health-promoting efficacies. However, mostly available as a complex form. So, to increase the contents and nutritional value of the phenolic compounds, fermentation is most readily used in the food industry. Especially, the hydrolyzable tannins present in the pomegranate that can be liberated into monomolecular substances, which enhances biological activity. Thus, this study aims to convert hydrolyzable tannins to ellagic acid by fermentation using Tannin acyl hydrolase (TAH) and a novel bacteria strain Lactobacillus vespulae DCY75, respectively to investigate its effect on Estrogen receptor alpha (ERα) and estrogen receptor beta (ERβ) mRNA expression along with inflammation inhibition. As a result, the fermentation enhanced the ellagic acid content up to 70% by the synergetic effect of TAH and DCY75. Furthermore, fermented pomegranate (PG-F) increased cellular proliferation as well as upregulated the gene expression of estrogen regulators such as ERα, ERβ, and pS2 in breast cancer cell line (MCF-7), which commonly used to evaluate estrogenic activity. Moreover, to study the inflammation associated with low estrogen in menopause, we have analyzed the inhibition of nitric oxide (NO)/inducible nitric oxide synthase (iNOS) in RAW 264.7 cells. The PG-F juice did not exert any cytotoxicity in RAW 264.7 cells and inhibited NO production along with the downregulation of a major pro-inflammatory cytokine iNOS which indicates the anti-inflammatory potential of it. To sum it up, the fermented commercial pomegranate juice using a novel bacteria strain increased the amount of ellagic acid that the value added bioactive of pomegranate and it has significantly increased the estrogenic activity via upregulating estrogen related biomarkers expression and reduced the risk of related inflammation via NO/iNOS inhibition. This study could be a preliminary study to use fermented pomegranate as a potential health functional food after further evaluation.